THE EFFECT OF ANTICIPATION GUIDE STRATEGY ON STUDENTS’ READING COMPREHENSION - Mezia Kemala Sari; Lisa Rana Sari (Ta'dib, 2019)
This research focuses on the influence of anticipation guide strategy on students' reading comprehension at the twelfth grade of MA KM Muhammadiyah Padang Panjang, 2017/2018 Academic Year. The research design was an experimental research conducted to the Science class as the participants of the research. The instrument of this research was a multiple-choice test distributed as the pre-test and post-test. As the result, the students’ reading comprehension became significantly better after being taught by the anticipation guide strategy. It is found that the pre-test average score was 42.36, and after the treatment, the post-test average score was 75.7. The result shows that the anticipation guide strategy has significant influence on the student’s reading comprehension.